1996
DOI: 10.33584/jnzg.1996.58.2221
|View full text |Cite
|
Sign up to set email alerts
|

Plantain (Plantago lanceolata) - a potential pasture species

Abstract: Plantago lanceolata L. is a herb species with a broad distribution in grasslands throughout the temperate world. The leaf is highly palatable to grazing animals, providing a mineral- rich forage. The species is rapid to establish, grows on a wide range of agricultural soils and is tolerant of drought and of many common diseases and pests. Two productive upright cultivars of plantain have been bred, Grasslands Lancelot and the more erect winter active Ceres Tonic. Plantain contains a range of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 53 publications
(71 reference statements)
6
112
1
1
Order By: Relevance
“…Reported IVTD values for naturally occurring plantain species are 804 g kg −1 (Derrick et al, 1993), but no additional reports are available concerning plantain under rotational grazing conditions. Wilman and Riley (1993) and Stewart (1996) suggest that the effect of plantain on rumen microflora (i.e., slowing down the breakdown of the material) affects the results obtained by the conventional methods of IVTD analysis. The authors advise that a similar method to that used in this work may judge against plantain when compared with other forages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported IVTD values for naturally occurring plantain species are 804 g kg −1 (Derrick et al, 1993), but no additional reports are available concerning plantain under rotational grazing conditions. Wilman and Riley (1993) and Stewart (1996) suggest that the effect of plantain on rumen microflora (i.e., slowing down the breakdown of the material) affects the results obtained by the conventional methods of IVTD analysis. The authors advise that a similar method to that used in this work may judge against plantain when compared with other forages.…”
Section: Resultsmentioning
confidence: 99%
“…This variation can be associated with reproductive stages and maturity of plant parts (Buxton et al, 1985) and with the effects of grazing animals caused by treading and dung and urine depositions (Matches, 1992). Reproductive stages of Pennlate orchardgrass occur early in the spring, whereas chicory and plantain may flower later in the spring and summer (Castellano‐Cantero, 1997; Stewart, 1996). It is possible that differences in the timing to reproductive development are associated with nutritive values observed because most differences between the forbs and orchardgrass occurred in May.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although naturalized populations of P lanceolata can be found throughout the northeastern USA, Tonic and Lancelot plantain were developed in New Zealand from germplasm originating in northern Portugal and the north island of New Zealand, respectively (Stewart, 1996). On the basis of our results, neither improved cultivar appears to have sufficient winter hardiness to survive in northeastern pastures.…”
Section: Discussionmentioning
confidence: 99%
“…I mproved cultivars of forage chicory and narrow‐leaf plantain have received increasing attention as possible forage and pasture species for the northeastern United States because of their reported high productivity during periods of drought (Stewart, 1996; Belesky et al, 1999; Kunelius and McRae, 1999) and high nutritive value (Jung et al, 1996; Stewart, 1996; Barry, 1998; Belesky et al, 2000). Although naturalized populations of chicory and plantain exist throughout the northeastern USA, the improved cultivars that are currently available were selected for pasture production under New Zealand conditions (Rumball, 1986; Stewart, 1996; Rumball et al, 1997). Sanderson et al (2001) reported stand losses of 20 to 50% for chicory grown in central Pennsylvania and found that plantain died out completely within 2 yr in one experiment.…”
mentioning
confidence: 99%